O-GlcNAcilação de proteínas como um sensor de nutrientes sinalizando disfunção placentária na gestação hipertensiva - Passos Junior, Rinaldo Rodrigues dos (2022)
The protein O-GlcNAcylation is essential for a proper placental development and this post-translational modification is found to be disrupted in hypertensive disorders of pregnancy. The present study aimed to investigate the impact of hypertension on the protein O-GlcNAcylation and fetal-placental development throughout pregnancy. First, a non-systematic literature review was carried out, based on analyzes and interpretations of the existing scientific production to understand the involvement of OGlcNAc in the establishment of hypertension. Subsequently, we sought to characterize how O-GlcNAcylation of proteins affects placental function and fetal growth throughout pregnancy under hypertensive conditions. To achieve this, spontaneously hypertensive rats (SHR) and Wistar were divided into 14, 17, and 20 days of pregnancy (DOP) groups. On the 14th, 17th, and 20th DOP, placentas were collected and submitted to western blot, immunohistochemistry, and morphological analysis. OGlcNAc protein expression was lower in placentas from SHR compared to Wistar at 14 (p=0.003) and 20 DOP (p<0.0001). Reduced OGT (p=0.01) and OGA (p=0.002) enzymes expression was found on 14 DOP in SHR. Increased pre-implantation losses were found in SHR at 14, 17, and 20 DOP. SHR presented reduced fetal weight and increased small for gestational age fetuses on all DOP analyzed. Placental weight was increased in near-term SHR (p=0.006) whereas placental efficiency was decreased in SHR at 17 (p=0.01) and 20 DOP (p<0.0001). Morphological analysis showed reduced junctional zone area and labyrinth vasculature alterations on placentas from SHR in all DOP analyzed. Reduced placental O-GlcNAc content was found in both the junctional zone and labyrinth of the placentas from SHR. Decreased glycogen cell content in placental tissue from SHR at 14, 17, and 20 DOP. Moreover, GLUT1 expression was found to be decreased in placentas from SHR in all DOP. Collectively, these findings suggest that reduced protein O-GlcNAcylation, resulting from decreased placental nutritional apport, contributes to placental structural and functional derangement during hypertensive pregnancy, impairing fetal growth.